Safety of SGLT2 Inhibitors: A Pharmacovigilance Study from 2013 to 2021 Based on FAERS - Zhou, Xiang; Ye, Xiaofei; Guo, Xiaojing; Liu, Dongxu; Xu, Jinfang; Hu, Fangyuan; Zhai, Yinghong; Gao, Yongqing; Xu, Xiao; Dong, Ziwei; He, Jia (Frontiers in Pharmacology, 2021)
Background: Sodium-glucose co-transporter-2 inhibitors (SGLT2is) are widely used in clinical practice for their demonstrated cardiorenal benefits, but multiple adverse events (AEs) have been reported. We aimed to describe the distribution of SGLT2i-related AEs in different systems and identify important medical event (IME) signals for SGLT2i. Methods: Data from the first quarter (Q1) of 2013 to 2021 Q2 in FAERS were selected to conduct disproportionality analysis. The definition of AEs and IMEs relied on the system organ classes (SOCs) and preferred terms (PTs) by the Medical Dictionary for Regulatory Activities (MedDRA-version 24.0). Two signal indicators, the reported odds ratio (ROR) and information component (IC), were used to estimate the association between SGLT2is and IMEs. Results: A total of 57,818 records related to SGLT2i, with 22,537 SGLT2i-IME pairs. Most SGLT2i-related IMEs occurred in monotherapy (N=21408, 94.99%). Significant signals emerged at the following SOCs: "metabolism and nutrition disorders" (N=9,103; IC025=4.26), "renal and urinary disorders" (3886; 1.20), "infections and infestations" (3457; 0.85). The common strong signals were observed in diabetic ketoacidosis, ketoacidosis, euglycaemic diabetic ketoacidosis and Fournier's gangrene. Unexpected safety signals such as Cellulitis, osteomyelitis, cerebral infarction and nephrolithiasis were detected. Conclusion: Our pharmacovigilance analysis showed that a high frequency was reported for IMEs triggered by SGLT2i monotherapy. Different SGLT2is caused different types and the association strengths of IMEs, while they also shared some specific PTs. Most of the results are generally consistent with previous studies, and more pharmacoepidemiological studies are needed to validate for unexpected AEs. Based on risk-benefit considerations, clinicians should be well informed about important medical events that may be aggravated by SGLT2is.